Health Concerns as the Fundamental Dietary Choices for Potential Stunting Preventions: a Qualitative Study - Inne Soesanti; Taufiqurrahman Taufiqurrahman; Ani Intiyati; Sri Hidayati (Amerta Nutrition)
Background: Pasongsongan Village lies in the Regency of Sumenep on the Island of Madura. It is a village bordered on the north by the Java Sea which is abundant of fish majorly consumed by adults. Whereas, children under two years old are scarcely served with fish in their diets.